2-ALKEL-5-XLOR BENZIMIDAZOL HOSILALARINING MUQOBIL SINTEZ USULLARI - Raxmatov, Elyor; SAIDOV, Sarvar; ABDURAZAKOV, Askar (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The reactions were carried out with the participation of 4-chloro-2-nitroaniline and carboxylic acids. Using modern physical research methods, the structure of the newly synthesized substances 2-ethyl-5-chlorobenzimidazole and 2-propyl-5-chlorobenzimidazole was studied.